T HE I N V E STI GAT I ON OF T E A C HI N G GE OGR A P HY A N D U S I N G D I F FE R E N T ME THOD S (Conferencea, 2022)
T h i s a r t i c l e s t u d i e s t h e p r o b l e m s o f d i f f e r e n t m e t h o d s o f t e a c h i n g g e o g r a p h y. I t a l s o f i n d s o u t a p p r o p r i a t e i n n o v a t i v e m e t h o d s o f t e a c h i n g g e o g r a p h y.